-0.25*cos(x)+4*cos(2x)+2.25*cos(3x)+0.25*cos(4x)=0

Simple and best practice solution for -0.25*cos(x)+4*cos(2x)+2.25*cos(3x)+0.25*cos(4x)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homewo

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -0.25*cos(x)+4*cos(2x)+2.25*cos(3x)+0.25*cos(4x)=0 equation:


Simplifying
-0.25cos(x) + 4cos(2x) + 2.25cos(3x) + 0.25cos(4x) = 0

Multiply cos * x
-0.25cosx + 4cos(2x) + 2.25cos(3x) + 0.25cos(4x) = 0

Remove parenthesis around (2x)
-0.25cosx + 4cos * 2x + 2.25cos(3x) + 0.25cos(4x) = 0

Reorder the terms for easier multiplication:
-0.25cosx + 4 * 2cos * x + 2.25cos(3x) + 0.25cos(4x) = 0

Multiply 4 * 2
-0.25cosx + 8cos * x + 2.25cos(3x) + 0.25cos(4x) = 0

Multiply cos * x
-0.25cosx + 8cosx + 2.25cos(3x) + 0.25cos(4x) = 0

Remove parenthesis around (3x)
-0.25cosx + 8cosx + 2.25cos * 3x + 0.25cos(4x) = 0

Reorder the terms for easier multiplication:
-0.25cosx + 8cosx + 2.25 * 3cos * x + 0.25cos(4x) = 0

Multiply 2.25 * 3
-0.25cosx + 8cosx + 6.75cos * x + 0.25cos(4x) = 0

Multiply cos * x
-0.25cosx + 8cosx + 6.75cosx + 0.25cos(4x) = 0

Remove parenthesis around (4x)
-0.25cosx + 8cosx + 6.75cosx + 0.25cos * 4x = 0

Reorder the terms for easier multiplication:
-0.25cosx + 8cosx + 6.75cosx + 0.25 * 4cos * x = 0

Multiply 0.25 * 4
-0.25cosx + 8cosx + 6.75cosx + 1cos * x = 0

Multiply cos * x
-0.25cosx + 8cosx + 6.75cosx + 1cosx = 0

Combine like terms: -0.25cosx + 8cosx = 7.75cosx
7.75cosx + 6.75cosx + 1cosx = 0

Combine like terms: 7.75cosx + 6.75cosx = 14.5cosx
14.5cosx + 1cosx = 0

Combine like terms: 14.5cosx + 1cosx = 15.5cosx
15.5cosx = 0

Solving
15.5cosx = 0

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Divide each side by '15.5'.
cosx = 0

Simplifying
cosx = 0

The solution to this equation could not be determined.

See similar equations:

| 6-2(x+5)=18-x | | y-7=0.7/2(x-5.2) | | 10x-4+5x+79=90 | | 2.8-y=6.9 | | (x+7)4=48 | | 3x-13+3x-10=12x-6 | | 56q^2-19qt-15t^2=0 | | 4(3x-3)=96 | | x*0.7=10 | | 6-5(7m+5)=86 | | 2x+3+x=x+3 | | 18q^2-39qt-189t^2=0 | | 6x-1x=6-6 | | 2i/3i | | 2w+2(1w+283)=19 | | 5p-95p+119p-p=151 | | 3[x+5]=27 | | 8x^2+10x+25= | | 2(3a+1)=5(a-1) | | 66-2r+1=3r-5(r-2) | | F(10.5)= | | 28+x=14 | | 6=x-3/2 | | 2(p+5)-3(p-7)=43 | | (9x^7)(-8x^5)=0 | | 10(d+9)=210 | | 7x-7-5x=2 | | 40-[3c+4]=4[c+5]+c | | 40-[3c+4]=[c+5]+c | | 4m-3=6m+5 | | -7t+4=-10t-14 | | 4[m+4]=40 |

Equations solver categories